FATTY LIVER DISEASE: SOME CHALLENGES OF STEATOMETRY (REVIEW) - Olga V. Kovaleva; Larysa V. Demeshkina; Victoria B. Yagmur; Elvira V. Zygalo; Аlla A. Kovaleva; Nadiya P. Dementiy; Теtiana О. Skorochod (Клінічна та профілактична медицина)
Introduction. The ultrasound hepatic steatometry is not only noninvasive, but also quite promising instrumental method for quantitative assessing and grading hepatic steatosis. However, there are some unclear aspects of this method. Aim. To compare the results of ultrasound hepatic steatometry for the quantitative assessment and grading of hepatic steatosis through a review of the research literature.